Implementasi Pasal 17 Undang-Undang Pokok Agraria Terhadap Batas Luas Maksimum Kepemilikan Tanah Pertanian Di Desa Girisako Kecamatan Logas Tanah Darat Kabupaten Kuantan Singingi - Sulik Rahayu; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Under Article 7, and Article 17 of the BAL states that the possession of land exceeding the limit is not permitted. The purpose of this regulation is to avoid the practice of landlords and to enhance the lives of farmers. This article is described further in Law no. 56 Prp Year 1960 About Stipulation of Land Area of Agriculture. In that Article stipulates that a person or persons in whose life a family together shall only be allowed to control the land of his own and that of the other person or his own with the other person whose total shall not exceed the maximum limit specified in the Law -What. With regard to the population, area and other factors areas are categorized quite densely ie 250-400 inhabitants per Km can only have land not more than 7.5 Ha for rice field and 9 Ha for dry land. However, the facts are still found that some people owning agricultural land exceed the maximum limit set by the law.The problem that the author made the basis in the study is how the implementation of the determination of agricultural land in the village of Girisako, how the legal effect on land ownership exceeds the maximum limit in the village girisako, and what government efforts in dealing with ownership of land exceeding the maximum limit in the village girisako. The research method used is descriptive sociological juridical. Source of data used in this research that comes from primary and secondary data. Data analysis uses qualitative data analysis and draw conclusions with deductive methods.The results of this study indicate the implementation of Article 17 of the BAL on the maximum limit of land ownership in the village girisako still a lot happening. This is due to public ignorance of regulations on the maximum agricultural land. The lack of supervision and the absence of government efforts is also a very important factor in the enforcement of this regulation. The conclusion of this research is that the government should review the regulation on the determination of agricultural land area. The land office needs to monitor the control of agricultural land so that in the future the implementation of the maximum limit of agricultural land can be done well.Keywords: Implementation-Limit Maximum Area- Agricultural Land